Asylum seekers and the role of the acute care physician - Kevin Molyneux; Elizabeth Singer (Journal of the American College of Emergency Physicians Open)
Abstract There has been a recent influx of migrants and asylum seekers to the United States. They often arrive with poor social support and an inability to access reliable health care. This can lead to overutilization of emergency departments (ED) while awaiting legal proceedings. With asylum seekers in all 50 states, it is important for emergency physicians (EP) to understand the barriers to care and difficulties asylum seekers face, and to gain tools to improve both migrants’ and community health. Migration and experiences within the United States can worsen pre‐existing health conditions. EPs are uniquely positioned to screen for acute pathology and link people to care. Psychiatric illnesses may present differently in asylum seekers. EPs must understand the sequalae of trauma to address it. EPs must also be aware of legal protections for asylum seekers to care for these patients, and recognize challenges faced by the population to mitigate health disparities.